2015
DOI: 10.1063/1.4922920
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of linear HC5H and cumulene carbene H2C5

Abstract: The 1 3 Σ − u ← X 3 Σ − g transition of linear HC 5 H (A) has been observed in a neon matrix and gas phase. The assignment is based on mass-selective experiments, extrapolation of previous results of the longer HC 2n+1 H homologues, and density functional and multi-state CASPT2 theoretical methods. Another band system starting at 303 nm in neon is assigned as the 1 1 A 1 ←  X 1 A 1 transition of the cumulene carbene pentatetraenylidene H 2 C 5 (B). C 2015 AIP Publishing LLC. [http://dx

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 40 publications
1
50
1
Order By: Relevance
“…10 Within C 5 H 2 elemental composition, the elusive aromatic carbene, 2-methylenebicyclo[1.1.0]but-1(3)-en-4-ylidene (9; see Figure 1), also contains a transannular C-C bond but less attention has been paid to this molecule. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Of note, for the confirmation of four C n H 2 carbenes in non-terrestrial environments, [1][2][3][4] identification of the same in laboratories (terrestrial environments) is a crucial factor. 1,11,[25][26][27] Therefore, considering the astrochemical relevance, available laboratory astrophysics data, and enhancing our understanding of structure and bonding of various C n H 2 isomers, where, n = 2, 28 3, 1,2,24,25,29-33 4, 3,27,[34][35][36] 5, 11-24 6, 4,11,34-37 7, 12,24,38-49 8, 34,35,39,50 9, 12,24,38,39,41,43,[51][52][53] etc., in this work, the electronic structures and spectroscopic properties of two additional singlet low-lying C 5 H 2 isomers, buta-1,3-diynylcarbene (6) and 9, have been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Within C 5 H 2 elemental composition, the elusive aromatic carbene, 2-methylenebicyclo[1.1.0]but-1(3)-en-4-ylidene (9; see Figure 1), also contains a transannular C-C bond but less attention has been paid to this molecule. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Of note, for the confirmation of four C n H 2 carbenes in non-terrestrial environments, [1][2][3][4] identification of the same in laboratories (terrestrial environments) is a crucial factor. 1,11,[25][26][27] Therefore, considering the astrochemical relevance, available laboratory astrophysics data, and enhancing our understanding of structure and bonding of various C n H 2 isomers, where, n = 2, 28 3, 1,2,24,25,29-33 4, 3,27,[34][35][36] 5, 11-24 6, 4,11,34-37 7, 12,24,38-49 8, 34,35,39,50 9, 12,24,38,39,41,43,[51][52][53] etc., in this work, the electronic structures and spectroscopic properties of two additional singlet low-lying C 5 H 2 isomers, buta-1,3-diynylcarbene (6) and 9, have been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, high-level coupled-cluster (CC) calculations including anharmonic vibrational frequencies and spectroscopic parameters have been missing in the literature for isomers 6 and 9. 14,15,[17][18][19][20][21][22][23][54][55][56][57][58][59][60][61][62] The theoretical work done here may assist the molecular spectroscopists in the detection and characterization of these elusive molecules in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In astrophysics and astrochemistry a fundamental question regards the nature of the carriers of diffuse interstellar bands observed in astronomical spectroscopy. Small carbon clusters such as linear chains or rings of sp-hybridized carbon and up to fullerenes are considered as candidates and laboratory investigations are widely used to study molecular and carbon aggregates in the gas phase with the aim of assigning observed bands to specific species, as recently shown by P. Maier and co-workers [8,9]. Despite the interest in sp-carbon, many aspects of the formation mechanisms are still open and much experimental work is needed to unveil optimal conditions for sp-carbon growth and to develop effective production techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several of them could be recognized among the discharge products of the (partly decomposed) 1, 6-heptadiyne precursor, e.g., cis-and trans-1-vinylpropargyl C 5 H 5 (Reilly et al 2009b), 1, 4-pentadienyl C 5 H 7 , benzocyclopropenyl C 7 H 5 (Maity et al 2015b), benzyl C 7 H 7 (Foster & Miller 1989), 1-phenylpropargyl C 9 H 7 (Reilly et al 2009a), and 1-indanyl C 9 H 9 Maity et al 2015a).  Furthermore, we observed the triplet chains HC 5 H and HC 7 H (Steglich et al 2015;Ding et al 2003), as well as previously unidentified species on masses corresponding to C 7 H 5 , C 7 H 7 , C 7 H 9 , C 8 H 9 , C 9 H 5 , and C 9 H 9 . The new C 9 H 5 and C 9 H 9 electronic absorptions, the strongest of which seem to agree with a few very weak DIBs, are presented in the following subsections.…”
Section: Resultsmentioning
confidence: 83%